A Quality Scorecard for the Administration of Online Education Programs - Shelton, Kaye (Online Learning, 2010)
As the demands for public accountability increase for the higher education, institutions are seeking methods for continuous improvement in order to demonstrate quality within programs and processes, including those provided through online education. A six round Delphi study was undertaken with 43 seasoned administrators of online education programs who agreed upon 70 quality indicators that administrators should examine within their programs to evaluate quality. A method for scoring was also developed. The original set of quality indicators from the Institute for Higher Education Policy study, Quality on the Line: Benchmarks for Success in Internet-Based Distance Education (2000) were used as a starting point and determined still valid in 2010, with modifications. The study resulted in a quality scorecard for the administration of online education programs.